PCB126 induced toxic actions on liver energy metabolism is mediated by AhR in rats. (30th January 2022) - Eti, Nazmin Akter; Flor, Susanne; Iqbal, Khursheed; Scott, Regan L.; Klenov, Violet E.; Gibson-Corley, Katherine N.; Soares, Michael J.; Ludewig, Gabriele; Robertson, Larry W.
Highlights: PCB126 caused weight loss, hypoglycemia, lower IGF1, reduced NEFA levels in rats. Sex-specific liver pathology and changes in gene expression were observed. PCB downregulated genes in glucose production pathways, particularly in male rats. Genes of fatty acid oxidation and serum cholesterol were more affected in females. Knocking out AhR completely prevented PCB126 alterations. Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor involved in the regulation of biological responses to more planar aromatic hydrocarbons, like TCDD. We previously described the sequence of events following exposure of male rats to a dioxin-like polychlorinated biphenyl (PCB) congener, 3, 3′, 4, 4′, 5-pentachlorobiphenyl (PCB126), that binds avidly to the AhR and causes various types of toxicity including metabolic syndrome, fatty liver, and disruption of energy homeostasis. The purpose of this study was, to investigate the role of AhR to mediate those toxic manifestations following sub-acute exposure to PCB126 and to examine possible sex differences in effects. For this goal, we created an AhR knockout (AhR-KO) model using CRISPR/Cas9. Comparison was made to the wild type (WT) male and female Holtzman Sprague Dawley rats. Rats were injected with a single IP dose of corn oil vehicle or 5 μmol/kg PCB126 in corn oil and necropsied after 28 days. PCB126 caused significant weight loss, reduced relative thymus weights, and increased relative liver weights in WT male and female rats, but not in AhR-KO rats. Similarly, significant pathologic changes were visible which included necrosis and regeneration in female rats, micro- and macro-vesicular hepatocellular vacuolation in males, and a paucity of glycogen in livers of both sexes in WT rats only. Hypoglycemia and lower IGF1, and reduced serum non-esterified fatty acids (NEFAs) were found in serum of both sexes of WT rats, low serum cholesterol levels only in the females, and no changes in AhR-KO rats. The expression of genes encoding enzymes related to xenobiotic metabolism (e.g. CYP1A1 ), gluconeogenesis, glycogenolysis, and fatty acid oxidation were unaffected in the AhR-KO rats following PCB126 exposure as opposed to WT rats where expression was significantly upregulated (PPARα, females only) or downregulated suggesting a disrupted energy homeostasis. Interestingly, Acox2, Hmgcs, G6Pase and Pc were affected in both sexes, the gluconeogenesis and glucose transporter genes Pck1, Glut2, Sds, and Crem only in male WT-PCB rats. These results show the essential role of the AhR in glycogenolysis, gluconeogenesis, and fatty acid oxidation, i.e. in the regulation of energy production and homeostasis, but also demonstrate a significant difference in the effects of PCB126 in males verses females, suggesting higher vulnerability of glucose homeostasis in males and more changes in fatty acid/lipid homeostasis in females. These differences in effects, which may apply to more/all AhR agonists, should be further analyzed to identify health risks to specific groups of highly exposed human populations.